Pengaruh ROA, ROE dan EPS Terhadap Harga Saham Pada Perusahaan Subsektor Kesehatan Yang Terdaftar di BEI 2015-2021 - Diah Yudhawati; Asti Marlina; Edwin Darmawan Darmawan (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This research aims to determine the effect of Return On Asset (ROA) Return On Equity (ROE) and Earning Per share (EPS) on Stock Price, which is tested partially and simultaneously. By using quantitative methods. The subjects of this study were health subsector companies listed on the IDX during the 2015-2021 period. Data collection was carried out using the documentation method, which was then analyzed using multiple linear regression analysis. The results of this study indicate that (1) Return On Asset (ROA) partially has a positive and significant effect on stock prices in health subsector companies for the 2015-2021 period with an effect of 17%, (2) Return On Equity (ROE) partially has a positive and significant effect on stock prices in health subsector companies for the 2015-2021 period with an effect of 14%, (3) Earning Per Share (EPS) partially has a positive and significant effect on stock prices in health subsector companies for the 2015-2021 period with an effect of 18.1%. (4) Return On Asset (ROA), Return On Equity (ROE), Earning Per share (EPS) simultaneously have a positive and significant effect on stock prices in health subsector companies for the 2015-2021 period with an effect of 28.7%.